2021
DOI: 10.1007/s40747-021-00274-4
|View full text |Cite
|
Sign up to set email alerts
|

Attention neural collaboration filtering based on GRU for recommender systems

Abstract: The collaborative filtering method is widely used in the traditional recommendation system. The collaborative filtering method based on matrix factorization treats the user’s preference for the item as a linear combination of the user and the item latent vectors, and cannot learn a deeper feature representation. In addition, the cold start and data sparsity remain major problems for collaborative filtering. To tackle these problems, some scholars have proposed to use deep neural network to extract text informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Early approaches to recognize statements included rule-based and machine-learning approaches. Reference [12] chose multi-layer perceptron neural networks and LSTM models to extract utterances in medical records; [13] used LSTM models to recognize utterances in the medical field; [14] based on CNN was used to identify utterances in combat documents. Reference [15] constructed a CRFs-based product alias recognition model for manually annotated ancient materials of Fangzhi; [16] recognized place names in Zuo Shi Zhuan of the Spring and Autumn Period based on CRFs and MEMM, and used e State Language [17]as a validation corpus, and found that CRFs outperformed MEMM [18] used a Bi LSTM-CNN-CRF model for entity extraction as the basis for constructing a Chinese historical knowledge graph.…”
Section: Related Workmentioning
confidence: 99%
“…Early approaches to recognize statements included rule-based and machine-learning approaches. Reference [12] chose multi-layer perceptron neural networks and LSTM models to extract utterances in medical records; [13] used LSTM models to recognize utterances in the medical field; [14] based on CNN was used to identify utterances in combat documents. Reference [15] constructed a CRFs-based product alias recognition model for manually annotated ancient materials of Fangzhi; [16] recognized place names in Zuo Shi Zhuan of the Spring and Autumn Period based on CRFs and MEMM, and used e State Language [17]as a validation corpus, and found that CRFs outperformed MEMM [18] used a Bi LSTM-CNN-CRF model for entity extraction as the basis for constructing a Chinese historical knowledge graph.…”
Section: Related Workmentioning
confidence: 99%
“…Time aware recommender systems are a subset of Context-aware recommender systems that focus on using time as contextual information to identify overlapping networks among users and aid in reducing the effect of sparsity [37]. Xia et al [38] proposes an attention based neural collaboration filtering for recommender systems, where long-distance dependent information and key information are provided as attention to the neural network to handle the cold start and data sparsity issues. Personalised recommendations is obtained using a autoencoder with attention mechanism, proposed in [9] where it gathers context information into the madel but lacks its accuracy in sparsity and cold start problem.…”
Section: Context-aware Recommender Systems That Uses Contextual Model...mentioning
confidence: 99%
“…The attention mechanism in deep learning is similar to the human visual attention mechanism, whose goal is to select information that is more critical to the current task from a lot of information. It has brought many breakthroughs to the fields of natural language processing [28][29][30] and computer vision [31,32]. Recently, many attentionbased methods have been designed to strengthen the feature representation capabilities of CNNs in image classification tasks [33][34][35].…”
Section: Attention Mechanismmentioning
confidence: 99%